2022
DOI: 10.1186/s12870-022-03468-1
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of the rice transcriptome and lipidome reveals lipid metabolism plays a central role in rice cold tolerance

Abstract: Background Rice (Oryza sativa L.) is one of the most widely grown food crops, and its yield and quality are particularly important for a warm-saturated diet. Cold stress restricts rice growth, development, and yield; however, the specific mechanism of cold tolerance in rice remains unknown. Results The analysis of leaf physiological and photosynthetic characteristics showed that the two rice varieties were significantly affected by cold stress, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…GO enrichment analysis indicated that the 1,018 targets that were negatively correlated with parameters of air temperature included a significantly higher proportion of genes related to ‘fatty acid beta-oxidation’ ( Table 5 ). This result appears to be consistent with those of previous reports of peanut ( Arachis hypogaea L.) [ 68 ] and rice ( Oryza sativa L.) [ 69 ], which exhibited up-regulation of genes related to fatty acid beta-oxidation under cold stress. Up-regulated expression of multiple beta-oxidation genes during germination was also reported in Tung tree ( Vernicia fordii , Hemsl.)…”
Section: Discussionsupporting
confidence: 93%
“…GO enrichment analysis indicated that the 1,018 targets that were negatively correlated with parameters of air temperature included a significantly higher proportion of genes related to ‘fatty acid beta-oxidation’ ( Table 5 ). This result appears to be consistent with those of previous reports of peanut ( Arachis hypogaea L.) [ 68 ] and rice ( Oryza sativa L.) [ 69 ], which exhibited up-regulation of genes related to fatty acid beta-oxidation under cold stress. Up-regulated expression of multiple beta-oxidation genes during germination was also reported in Tung tree ( Vernicia fordii , Hemsl.)…”
Section: Discussionsupporting
confidence: 93%
“…Cold stress as a major environmental factor severely limits the growth and development, as well as the improvement of yield and quality, in rice. According to the degree of cold stress, the plant undergoes corresponding changes at the phenotypic, physiological, and molecular levels to respond to the low temperature, including photosynthetic rate, redox homeostasis, hormone signal transduction, transcriptional regulation, and posttranslational modification [4,7]. In this study, we integrated the transcriptomic analysis and genome data to reveal the rapid and dramatic transcriptional reprogramming process in the early stage of cold treatment and predict the cold sensitivity-related candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is one of the major cereal crops in the world and plays a key role in global food security [1]. Cold damage as a kind of natural disaster is often encountered during the whole growth and development of rice, and limits its growth, geographical distribution, yield, and quality [2][3][4]. Especially for rice seedlings, low temperature causes damage to leaves and roots, a withered state, and even death [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that unsaturated fatty acids are closely associated with chilling responses. Under low-temperature conditions, cold-tolerant varieties have higher membrane lipid unsaturation and unsaturated fatty acid content, enabling the plant to maintain a certain degree of stability and fluidity of the membrane system ( Liu et al., 2022 ). For instance, 3-day cold or dark treatment significantly induces eicosapentaenoic acid biosynthesis ( Chua et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%